Cassava Starch and Nano Zinc Oxide Biodegradable Films as Packaging Materials - Helia B. Leon-Molina; Sergio E. Plazas Jimenez (Chemical Engineering Transactions)
In the mid-20th century polymeric materials were introduced, since then, have gained significant ground in different fields. Their low density, combined with mechanical, thermal, optical, and chemical properties sufficient to meet various needs, has allowed them to replace conventional ceramic and metallic materials. However, the mass adoption of their use, coupled with challenges related to their recovery, degradation, and improper disposal, has led to their accumulation in natural environments. A potential solution lies in the use of biodegradable polymers to replace those still in use today, especially in single-use products. However, this requires improvements in their properties. In this study, films were produced from gelatinized starch formulations with zinc oxide (ZnO) nanoparticles in concentrations ranging from 0% to 1.0% w/w. The obtained films were characterized using Fourier Transform Infrared (FTIR) spectroscopy, tensile strength tests, scanning electron microscopy (SEM), and their biodegradability was assessed in soil (black earth). The results showed that ZnO formulations exhibited lower modulus, lower tensile strength, and higher elongation than plasticized starch films, as well as potential interactions between ZnO nanoparticles and the polymeric matrix, particularly at concentrations of 0.4% w/w and 0.6% w/w. Furthermore, the films containing ZnO showed damage and deterioration in soil at 40°C and humidity levels between 40% and 60%, with monitoring over 52 days. These results allow us to continue the search for additives and formulations that improve the properties of plasticized starch with the purpose of using it as packaging material at an industrial level.